English laughter in Polish. Problems with humour in the translations of works by Charles Dickens - Aleksandra Budrewicz (Napis)
This article focuses on the Polish translations of Charles Dickens's prose, with a specific emphasis on the humorous aspects. It examines the issue using the character Wilkins Micawber from the novel David Copperfield (1849–1850), considered one of Dickens's best comic creations. A comparison of the original with several translations that differ in style: Wilhelmina Zyndram-Kościałkowska (1889), Cecylia Niewiadomska (1927) and Karolina Beylin (1989) shows that Dickensian humour is most easily conveyed through situational comedy (theatricalisation of characters' behaviour), while it proves particularly more challenging to find Polish equivalents of verbal comedy, cultural context and the realities of the period.